Internet application Mozilla localization and using in teaching - Grigas, Gintautas; Jevsikova, Tatjana (Lietuvos matematikos rinkinys, 2002)
The analysis of Intemet application Mozilla using at school is presented. The reasons to discuss this topic are following: 1) the programs' suite was localized (menu, dialog boxes and other strings and documentation are translated and the program is adapted for its proper matching to Lithuanian environment); 2) using one Mozilla package for teaching Intemet topics instead of separated Internet applications (web browser, HTML composer, e-mail and chat clients) has many advantages.The new features, added into Mozilla during its localization, are described, farther improvement possibilities are evaluated and a short curriculum is presented.